Analisis pemanfaatan fitur Track Changes pada MS.Word untuk mengetahui originalitas karya Mahasiswa - Seituni, Siti; Yuliana, Dyan; Suparto, Arico Ayani; Rahmawati, Weni Kurnia; Febriyanti, Anis (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Analysis on the benefits of technology has a good impact if users understand the benefits or usefulness of a feature. in learning is a complete element that underlies the usefulness in providing techniques, especially in a scientific work. One of the most commonly used word processing programmes is Microsoft Word, which has a